2006
DOI: 10.1007/s10661-006-1072-y
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Availability in Soil Amended with Composted Urban Solid Wastes

Abstract: A study was performed to evaluate the pH and the availability of Zn, Cu, Mn, Pb, and Ni in soil amended with increasing doses of composted solid wastes, collected in Rio de Janeiro, Rio de Janeiro State and in Coimbra, Minas Gerais State, Brazil. The influence of the time elapsed between compost application to the soil and the sampling of the plant growth substrate (soil + compost) for pH and metal availability analyses was also examined. The availability of heavy metals in the soil, in the compost and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 31 publications
2
63
0
4
Order By: Relevance
“…The basic properties were as follows: pH 7.60, organic matter 12.0%, total N 5.10%, available P 77.9 mg·kg . The compost was slightly alkaline, in agreement with the results of Jordão et al [21]. The higher pH is attributed to high concentrations of exchangeable bases in compost [24].…”
Section: Msw Compost Properties and Metal Concentrationssupporting
confidence: 89%
See 2 more Smart Citations
“…The basic properties were as follows: pH 7.60, organic matter 12.0%, total N 5.10%, available P 77.9 mg·kg . The compost was slightly alkaline, in agreement with the results of Jordão et al [21]. The higher pH is attributed to high concentrations of exchangeable bases in compost [24].…”
Section: Msw Compost Properties and Metal Concentrationssupporting
confidence: 89%
“…In most cases, increasing pH declines metal availability [25]. Consistent with other research [21], higher nutrient contents of organic matter and total N were found in compost. Organic matter contains large quantities of plant nutrient that act as a slow-release nutrient storehouse.…”
Section: Msw Compost Properties and Metal Concentrationssupporting
confidence: 89%
See 1 more Smart Citation
“…The average concentrations of plants from (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are, respectively: 0.012±0.01, 0.0006±0.003, 0.015±0.003, and 2.7±0.001 for Pb, Cd, As, and Hg.…”
Section: Resultsmentioning
confidence: 99%
“…The uptake of heavy toxic metals from soils by plants at high concentrations leads to subsequent accumulation along the food chain and may result in a greater health risk [14]. Some important supplements in the human body are influenced by consumption of food contaminated with heavy metals, causing decreased immunity, intrauterine growth retardation, disabilities associated with malnutrition, and a high prevalence of upper gastrointestinal cancer rates [15].…”
mentioning
confidence: 99%